Perkembangan Financial Technology (Fintech) dalam Digital Perbankan di Indonesia - Hani Harlan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The development of technology in the digital era has brought significant transformation in various sectors. One of the sectors affected is the financial sector in Indonesia. Financial Technology (fintech) in digital banking is the main driver in increasing financial inclusion and providing easy access to financial services for the community. Digital innovation in this sector not only facilitates transactions but also creates new business models that are more efficient and adaptive to consumer needs. This study aims to analyze the development of fintech in digital banking in Indonesia and assess its impact on the financial system and public behavior. The research method used is descriptive qualitative with a literature study approach and data analysis from trusted sources related to the development of the fintech industry in digital banking in Indonesia. The results show that fintech in digital banking makes a significant contribution in expanding access to financial services, improving operational efficiency, and encouraging innovation in the provision of financial products and services. However, challenges such as data security, financial literacy, and regulation remain key concerns. In conclusion, the development of fintech in digital banking in Indonesia shows great potential in supporting economic growth and financial inclusion.